1983
DOI: 10.1080/10408398209527346
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite, nitrite alternatives, and the control of clostridium botulinum in cured meats

Abstract: Historically, nitrite has been a component of meat-curing additives for several centuries. In recent years the safety of nitrite as an additive in cured meats has been questioned mainly because of the possible formation of carcinogenic nitrosamines. Nitrite has many important functions in meat curing including its role in color development, flavor, antioxidant properties, and antimicrobial activity. The inhibition of Clostridium botulinum growth and toxin production is an especially important antimicrobial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 214 publications
2
57
0
3
Order By: Relevance
“…However, the majority of studies concerning the antimicrobial properties of nitrites have been focused on C. botulinum in several meat products produced in various countries (EFSA, 2003). Nitrites show antibotulinal activity against both vegetative cells as well as spores of the pathogen in thermally processed meat products (Pierson and Smooth 1982). Despite the vast amount of research, the precise nitrites action against C. botulinum or other bacteria has not absolutely clarified in meat products.…”
Section: Microbiological Safetymentioning
confidence: 99%
“…However, the majority of studies concerning the antimicrobial properties of nitrites have been focused on C. botulinum in several meat products produced in various countries (EFSA, 2003). Nitrites show antibotulinal activity against both vegetative cells as well as spores of the pathogen in thermally processed meat products (Pierson and Smooth 1982). Despite the vast amount of research, the precise nitrites action against C. botulinum or other bacteria has not absolutely clarified in meat products.…”
Section: Microbiological Safetymentioning
confidence: 99%
“…Concentrations of nitrite previously found necessary to inhibit clostridial growth in liquid growth medium have ranged from 4-4mM at pH 7.0 to 7.0 mM at pH 7.5 (Roberts & Ingram, 1966;Perigo et al, 1967;Perigo & Roberts, 1968 ;Baird-Parker & Baillie, 1973 ;O'Leary & Solberg, 1976;Woods et al, 1981). We have similarly shown that C. sporogenes readily grow in liquid cultures in the presence of nitrite, at concentrations above those used in food preservation (Pierson & Smoot, 1981;Knight et al, 1987), i.e. >2-3 mM.…”
Section: Relevance Of Nitrite Concentrations Usedmentioning
confidence: 71%
“…The bacteriostatic action of NaN02 in these systems is enhanced when it is reduced by ascorbate (Tompkin et al, 1978a, b ;Pierson & Smoot, 1981). Perigo & Roberts (1968) found that when nitrite was heated with reinforced clostridial medium at pH 6-7, the nitrite disappeared and the medium became more inhibitory to clostridial growth.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrite is a very important ingredient in processed meats, owing to its contribution to color development, flavor, antioxidant properties, and the microbiological stability (1,2). Nevertheless, nitrite could potentially produce carcinogens and mutagenic N-nitrosamines and secondary or tertiary amines (3).…”
Section: Introductionmentioning
confidence: 99%